What should suppliers do to improve the relationship quality with their clients? -------- Empirical evidence from manufacturing sector of Shenzhen, China. - Luo, Bin (2007)
The aim of this research is to identify the functions of the supplier to the client firms and explore the impacts of these functions on the relationship quality. For the client firm, what functions of the supplier relationship are really expected and what functions are not so important? The answers to these questions may guide client firms in the selection of the strategic suppliers and guide the supplier firms on how to meet the demands of the client firms, resulting in a better cooperative relationship. In addition, other variables have impacts on the process in which the functions of supplier quality influence the relationship quality. The findings are as follows. The client firm with different nature of ownership does not perceive the direct functions of supplier relationship differently, but it perceives the indirect functions differently. Foreign invested firm values the long term development of the relationship with the supplier, implying that it emphasize the indirect functions of the supplier more than the state-owned or domestic private firm. Large firms have higher requirements on the indirect functions than medium sized and small firms. Foreign invested firms are easier to have trust in its supplier and make commitment with the supplier, thus enjoying higher relationship quality than state-owned or domestic private businesses. The duration of the relationship impacts the client on the perception of the functions of the supplier relationship. The longer cooperation history leads to the client's higher requirement on the cost function and the indirect functions and leads to the higher degree of trust of the client in the supplier. The functions of the supplier relationship significantly impact on the B2B relationship quality. The cost, quality, innovation development and market functions have more influences on the client's commitment with the supplier. The quality, social support and innovation development functions have more influences on the client's trust in the supplier. The quality, scout and market functions are negatively related to the conflict dimension of the relationship quality.